PELESTARIAN DAN MAKNA BUDAYA NYANGAHATN PADA UPACARA NAIK DANGO SUKU DAYAK KANAYATN - Endang, Agustinus; Khosmas, F. Y; Firmansyah, Haris (Universitas Tanjungpura, 2023)
This study aims to describe the Preservation and Cultural Meaning ofNyangahatn in the Naik Dango Ceremony of the Dayak Kanayatn Tribe inKeranji Paidang Village, Sengah Temila District, Landak Regency. This studyuses a qualitative method with a descriptive-ethnographic approach. Datacollection techniques used are observation, interviews and documentation. Thedata collection tools are observation guides, interview guides anddocumentation tools. The data analysis technique used is data reduction, datapresentation and conclusion. Testing the validity of the data is usingtriangulation which consists of triangulation of sources and triangulation oftechniques. The results of this study indicate: (1) Preservation of Nyangahatnin Oto Ledang hamlet is preserved through every implementation of traditionalceremonies and is carried out sacredly without reducing the value and meaningcontained therein. Therefore there is also a traditional ceremony, Nyangahatn,Nyangahatn as a prayer or prayer reading at each ceremony which will becarried out by the community and the next generation in Oto Ledang Hamlet.(2) The Nyangahatn process at the Naik Dangodi Ceremony of Oto LedangHamlet is divided into two parts and several places, namely Nyangahatn Mantaand Masak (raw and cooked). (3) the related meaning contained in NyangahatnAt Naik Dango Ceremony is an expression of gratitude for what farmers haveachieved in farming for one season, so that farmers hold the Naik DangoCeremony by conveying a prayer of thanksgiving, gratitude to Jubata for theresults harvest through prayers said by a Panyangahatn or called Nyangahatn.